CONFLICT RESOLUTION: A CASE STUDY OF THE SEPARATIST MOVEMENT IN THE SOUTHERN BORDER PROVINCES OF THAILAND - Lutfee Abdulmani (P3M STAIN Kudus, 2014)
This Undergraduate thesis tried to discuss about conflict resolution in the case of southern Thailand which are Pattani, Yala, and Narathiwat, known as an escalating and brutal conflict and long history of insurgency, the crisis has been conducted primarily on the basis of Malay ethnic nationalism with religion and politics as an additional factors. The violence has already had important political consequences in the failure of Prime Minister Thaksin’s government. The government tries to solve the problem and lunched a strategy based on increased public participation, economic development, apologizing for the past misdeeds of the security services, ending the blacklisting of Muslim and opens a dialogue with insurgents, but the violence remains. In this research, the writer use an extensive of relevant published materials such as books, journals, reports, newsletters, official website and other sources o a wide variety of topics related with the subject of the topic.